Brief Report: Bictegravir/Emtricitabine/Tenofovir Alafenamide Efficacy in Participants With Preexisting Primary Integrase Inhibitor Resistance Through 48 Weeks of Phase 3 Clinical Trials. (1st April 2022) - D'Antoni, Michelle L.; Andreatta, Kristen; Acosta, Rima; Martin, Hal; Chang, Silvia; Martin, Ross; White, Kirsten L.
Abstract : Background: Preexisting drug resistance limits the utility of HIV antiretroviral therapy. Studies have demonstrated safety and efficacy of bictegravir/emtricitabine/tenofovir alafenamide (B/F/TAF), including in patients with M184V/I substitutions. Setting: We investigated virologic outcomes through 48 weeks of B/F/TAF treatment in individuals with preexisting primary integrase strand transfer inhibitor resistance (INSTI-R). Methods: Preexisting INSTI-R was retrospectively evaluated from 7 B/F/TAF studies. INSTI-R was assessed by historical genotypes and/or baseline RNA or DNA sequencing. Viral loads were measured at all visits. Results: Preexisting primary INSTI-R substitutions were detected in 20 of the 1907 participants (1.0%). The 20 participants were predominantly male (75%), were Black (65%), had HIV-1 subtype B (85%), and had baseline median CD4 counts of 594 cells/mm 3 and median age of 52 years. Most of the participants (n = 19) were virologically suppressed at baseline and had one primary INSTI-R substitution, E92G, Y143C/H, S147G, Q148H/K/R, N155S, or R263K, +/−secondary substitutions. All suppressed participants maintained virologic suppression throughout 48 weeks without any viral blips. One treatment-naive participant had virus with Q148H+G140S that was fully sensitive to bictegravir but only partially to dolutegravir (phenotype <2.5-fold change and >4-fold change, respectively). With a baseline viral load of 30, 000 copies/mL, this participant was virologically suppressed by week 4 and maintained <50 copies/mL through week 48. Conclusions: This small cohort with primary INSTI-R achieved and/or maintained virologic suppression through 48 weeks of B/F/TAF treatment. Consistent with the potent in vitro activity of bictegravir against most INSTI-R patterns, B/F/TAF may be a potential treatment option for patients with select preexisting INSTI-R, if confirmed by further studies.